Alcohol consumption and factors associated with binge drinking among female university students of health area - Ana Karina Rocha Hora Mendonça; Carla Viviane Freitas de Jesus; Maria Bernadete Galrão de Almeida Figueiredo; Daisy Pereira Valido; Marco Antonio Prado Nunes; Sonia Oliveira Lima (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To evaluate the pattern of alcohol consumption and the prevalence and factors associated with binge drinking among university students of health-related courses in Aracaju, Sergipe, Brazil. Methods: A cross-sectional study was performed of 865 female students from two universities in the Brazilian Northeast. The instruments used were the AUDIT and a questionnaire used to collect sociodemographic data. The chi-square test and logistic regression were used, with statistical significance set at p-value < 0.05. Results: Risky alcohol consumption was evidenced in 16.4%, while the prevalence of binge drinking was 48.0%. Binge drinking was strongly associated with drunk driving (OR = 12.24) and living in a conflicting family environment (OR = 6.33). Binge drinking was a constant in students who engaged in fights, those who had problems with the law and among smokers. Conclusion: The high prevalence of risky alcohol consumption, binge drinking and the association of these with risky behaviors in students serve to guide future public policies on prevention.